Pfaffian Differential Equation and It’s Application in Thermodynamics and Dynamics - Kumar, Nand Kishor; Raikhola, Sher Singh (NUTA Journal, 2023)
This article provides a basic overview of the Pfaff function and equation. It also explains the concept/idea and method for solving the Pfaffian differential equation. The Pfaff differential equation has been shown to be useful in thermodynamics and dynamics.